Trend Assessment of Different Malariometric Parameters of Surat City: A Retrospective Study - D Jariwala1, Priyanka (International Journal of Scientific Research and Management (IJSRM), 2017)
Malaria is a life threatening disease caused by parasites of the genus Plasmodium that is transmitted to people through the bitesof infected mosquitoes. It is the leading cause of death in children under the age of 5 years and pregnant women, in developing countries.The present study was carried out with secondary data to assess the trend of malaria in terms of various malariometric parameters such asAnnual Blood Examination Rate (ABER), Annual Parasite Incidence (API), Slide Positivity Rate (SPR) and Slide Falcifuram Rate (SFR) ofSurat City. The analysis has shown that there is an overall declining trend in malaria in the city. The annual blood examination rate hasincreased from 2001 to 2014. The various malariometric indicators such as API, SPR and SFR have reduced drastically in the last decadeThis could imply that although there are different malaria control activities each year such as insecticide spraying, elimination of mosquitobreeding sites, distribution of Insecticide Treated Nets and malaria drugs to decrease mortality and morbidity of malaria, prevalence issustained by the continuous vigilance of local governing body that is Surat Municipal Corporation.